HYDRODYNAMIC MODELLING DEVELOPMENT FOR MEMBRANE FLOATS FLOATING PV AND IT'S IMPLEMENTATION ON STATION-KEEPING DESIGN FOR FLOATING PV AT THE NORTH OF SUMBA ISLAND, NTT - Ananda Taneli, Marvin
In this study, the complex membrane type floating PV model was simplified based on previous experiment by Jonathan Winsvold in 2018. The continuous membrane is modelled as five discrete elastic tori that are connected by elastic trusses in the radial direction. The elastic trusses elements have negligible inertia properties and its tension is configured to mimic the actual membrane stiffness. The experimental scale numerical model is validated against the experiment and theoretical results from literatures. Then, the full-scale structural diameter of 50 metres and torus cross-sectional diameter of 1.6 metres is modelled in the numerical set-up. In this study, the load from Solar PV Modules were inserted as additional mass per length on the tori to better represent the real-world condition. The model was then simulated in the time domain for 3 hours under environmental conditions including wind, current, and waves in the North of Sumba Island, East Nusa Tenggara. In order to understand the hydrodynamic behavior of the structure, a sensitivity study was qualitatively performed in the frequency domain. The sensitivity study was conducted by comparing the pretension on the membrane, 2 different mooring configurations, 2 environmental force directions, and mooring failure conditions. The sensitivity study on membrane pre-tension showed that the model was able to capture the characteristics of the membrane structure, where the stiffness of the membrane increased as the pre-tension increased. The comparison of mooring configurations and environmental force directions had only a slight effect on the outer torus. Furthermore, the mooring configuration with a pickup buoy (MC 2) was considered better than the mooring configuration without a buoy (MC 1) based on structural response and mooring tension. In the MC 2 configuration, redesigns were made to meet design criteria, and the impact of mooring failure was analyzed on the MC 2 configuration with the mooring that broke having the highest maximum tension. The result suggests the mooring line failure condition did not affect the structural response but increased the mooring tension on the lines that did not break.